Analysis of Drug Logistic Management in the Pharmaceutical Installation of the Health Office of North Sumatera Province - Meilan Sri Yanti Harahap; Megawati Megawati; Asriwati Asriwati (Newinera Publisher, 2020)
The purpose of this study was to analyze the logistics management of drugs in the pharmaceutical installation at the health office of the province of North Sumatra. This research method is qualitative.The informants in this study are all drug managers at the Provincial Health Office consisting of Key Informants 1 Head of the Pharmaceutical Section, 1 Health Service User Property Manager, 4 pharmaceutical installation staff and Supporting Informants of the Regency/city Health Office as goods users. The instruments used in this research are primary data from interviews and secondary data from reports that can be used as sources or references to support research data. Results. The results showed that the source of the budget came from the Regional Revenue And Expenditure Budget (APBD) and APBN (State Revenue and Expenditure Budget) funds. The number of human resources in the pharmacy section in drug management in the pharmaceutical installation of the Sumatra Provincial Health Office is 18 people. The distribution method is carried out in 2 ways, namely the Regency / City Health Service which picks up directly from the North Sumatra Provincial Health Office or the North Sumatra Provincial Health Office who sends it to the Regency/City Health Office. All drug needs at the Regency/city Health Office are fully met and the supply is sufficient. Drug logistics management at the Pharmacy Installation of the North Sumatra Provincial Health Office has been running well, this is a sign of the availability of good and sufficient drugs.